Pengaruh Kemampuan Executive Functioning Terhadap Kemampuan Representasi Matematis - Silvi Uswatun Nisa; Rostina Sundayana (Jurnal Padegogik, 2023)
In learning mathematics, teachers are faced with different mathematical abilities, characters and mental skills of students. Executive functioning skills are a combination of mental skills needed by individuals to adapt and plan to achieve goals in an action. Differences in students' abilities and skills will certainly affect the achievement of students' mathematical representation abilities. The ability of mathematical representation is the ability of students to describe a mathematical concept, and to communicate it, either in the form of images, mathematical expressions, or in the form of words. This study aims to analyze the effect of executive functioning on mathematical representation abilities. The research was carried out at SMAN 5 Garut, with the subject of class XI MIPA 1 for the 2022-2023 academic year. The research method used is comparative-associative explanatory research. From the results of the study it was revealed that executive functioning abilities: Self-Control, Self-Monitor/Self-Evaluation, Task Initiative, Working and Memory Attention, Emotional Control, Planning and Time Management and Organization have no significant effect on the ability of mathematical representation.